Drospirenone detected in postmortem blood of a young woman with pulmonary thromboembolism: A case report and review of the literature. Issue 2 (March 2015) - Idota, Nozomi; Kobayashi, Masaki; Miyamori, Daisuke; Kakiuchi, Yasuhiro; Ikegaya, Hiroshi
Highlights A young woman with fatal pulmonary thromboembolism was believed to be taking YAZ. Drospirenone contained in YAZ was not detected through UPLC–MS screening. Drospirenone was detected through performing subsequent SIR mode assay analysis. The risk of venous thromboembolism from YAZ is not lower than conventional drugs. It is important for forensic scientists to confirm prescribed drugs in autopsies.